2016
DOI: 10.1038/srep37858
|View full text |Cite
|
Sign up to set email alerts
|

In silico clustering of Salmonella global gene expression data reveals novel genes co-regulated with the SPI-1 virulence genes through HilD

Abstract: A wide variety of Salmonella enterica serovars cause intestinal and systemic infections to humans and animals. Salmonella Patogenicity Island 1 (SPI-1) is a chromosomal region containing 39 genes that have crucial virulence roles. The AraC-like transcriptional regulator HilD, encoded in SPI-1, positively controls the expression of the SPI-1 genes, as well as of several other virulence genes located outside SPI-1. In this study, we applied a clustering method to the global gene expression data of S. enterica se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 80 publications
(132 reference statements)
2
15
0
Order By: Relevance
“…Typhimurium. HilD acts as a regulatory hub for virulence coordinating the expression of several virulence factors encoded inside and outside SPI-1 [18,28,4042]. Indeed, in this report we provide further corroboration of the role of HilD in regulating SPI-2 gene expression.…”
Section: Discussionsupporting
confidence: 76%
“…Typhimurium. HilD acts as a regulatory hub for virulence coordinating the expression of several virulence factors encoded inside and outside SPI-1 [18,28,4042]. Indeed, in this report we provide further corroboration of the role of HilD in regulating SPI-2 gene expression.…”
Section: Discussionsupporting
confidence: 76%
“…HilC and RtsA are AraC-like transcriptional regulators that bind the same DNA sequence recognized by HilD; HilC is encoded within SPI-1, whereas RtsA is encoded in another island. HilD also controls the expression of many other virulence genes located outside SPI-1, including acquired and ancestral genes, directly, or indirectly through HilA, InvF or other regulators (12,(17)(18)(19)(20)(21)(22)(23)(24)(25). In agreement with its role as a master transcriptional regulator for a high number of genes, the expression, concentration and activity of HilD is tightly controlled.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we identified a set of novel genes that are co-expressed with the SPI-1 genes in S . Typhimurium, by an in silico global expression analysis 42 . The characterization of some of these genes revealed a strong link between the co-expression with SPI-1 and the regulation by HilD.…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium. The expression of genes known to be directly controlled by HiD, such as hilA , can be induced in E. coli K-12 when HilD is present 42 . Therefore, to further test if HilD regulates grhD1 indirectly, the activity of the grhD1-cat fusion was determined in the E. coli MC4100 strain carrying the pK6-HilD plasmid, grown in LB.…”
Section: Resultsmentioning
confidence: 99%